177k views
0 votes
Substitution Method
x-y=9
x+y=7

User Anpan
by
5.2k points

2 Answers

2 votes

Answer:

Explanation:

Substitution method can be applied in four steps.

Solve one of the equations for either x = or y = .

Substitute the solution from step 1 into the other equation.

Solve this new equation.

Solve for the second variable. ...

Step 1: Solve one of the equations for either x = or y =

User Saliha
by
5.0k points
2 votes

Answer:

(8, - 1 )

Explanation:

Given the 2 equations

x - y = 9 → (1)

x + y = 7 → (2)

Rearrange (1) expressing x in terms of y by adding y to both sides

x = 9 + y → (3)

Substitute x = 9 + y into (2)

9 + y + y = 7

9 + 2y = 7 ( subtract 9 from both sides )

2y = - 2 ( divide both sides by 2 )

y = - 1

Substitute y = - 1 into (3) for corresponding value of x

x = 9 - 1 = 8

Solution is (8, - 1 )

User Nishant Jani
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.